Constructing the 'Great Menace': Canadian Labour's Opposition to Asian Immigration, 1880–1914 - Goutor, David (Canadian Historical Review, 2007)
Canadian labour's agitation against Asian immigration in the late nineteenth and early twentieth centuries has received a considerable amount of scholarly attention. Many historians have highlighted labour's concerns about Asian competition in the labour market, while others have explored the pervasiveness of anti-Asian racism in most segments of Canadian, and especially British Columbian, society. But these factors – while important – do not sufficiently explain labour's antipathy to Asians. They particularly fail to account for the unity against Asian immigration between unionists in different regions, the influence of campaigns for exclusion in other countries, and the class content of labour's anti-Asian rhetoric. Another under-explored issue is whether unionists approached Asians in the same way as other immigrants, minorities, and oppressed groups. Drawing on the growing literature on racialization, and focusing primarily on the 1880s, when labour's views on Asian immigration became well established, this article shows how Asians were set apart from any groups with whom labour might have sympathy or common cause. Asians were associated with oppressive forces, particularly of the emerging industrial capitalist system. This association can be seen in many of labour's stereotypes of Asians as industrial slaves, ruthless competitors in the economy, and threats to white women. These stereotypes also set Asians up as polar opposites to the basic class, race, and gender identity that labour leaders sought to foster.
Keywords: Capitalism; Immigrants; Industry; Labour; Minorities; Race; Unions; Working class